PROBLEMATIKA DAKWAH DI NEGERI MINORITAS MUSLIM - Aziz, Muchlis; Zulfadli, Zulfadli; Nurainiah, Nurainiah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Allah created human beings with religious instincts, namely the religion of monotheism (Islam). The Koran claims that the religious teachings it introduces are compatible with all humans. Islam as a truth, then Islam must be spread throughout the world and this is the responsibility of every human being on this earth as a caliph. Every Muslim, of course, has an obligation to propagate the da'wah of Islam, even though they experience various kinds of obstacles and obstacles. This certainly applies to Muslims who are in Australia with a Muslim population in Australia currently around one million people. With this quantity of Muslim citizens in Australia, Islamic da'wah is needed to transfer the spread of the values of Islamic da'wah to all Muslims. One way is by establishing Islamic-based educational institutions. At present, the Islamic Council in Australia is intensively building educational facilities based on Islamic education, with the aim of making it easier for them to transfer Islamic knowledge to the Islamic community in Australia. Spreading Islamic da'wah in the current era is full of challenges, especially spreading Islamic da'wah in Muslim minority countries such as Australia. Australia is a country that has a broad geographical position, and upholds the values of freedom, in that case the Australian government guarantees plurality. In the midst of Australia's position that promotes freedom, Islam must be able to place itself in the midst of society and also practice the teachings of Islam in a pluralistic society. Australia has approximately 100 beliefs/religions, with Islam as a minority religion, so the challenge of Islamic da'wah is to keep on doing good communication and living side by side with the differences.Keywords: Community, Da'wah and Muslim.